Pengaruh Lingkungan Kerja, Motivasi Kerja, Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada CV. Surya Wannas Cilacap - Siti Nurjanah (Jurnal Bisnis dan Kewirausahaan, 2024)
This research is to analyze the influence of work environment, work motivation and work discipline on employee performance in CV. Surya Wannas Cilacap on the influence of work environment, work motivation, and work discipline on employee performance on CV. Surya Wannas Cilacap. The results obtained show that the work environment has a significant effect on employee performance, this can be proven by the sig value. the count is greater than 0.05 ie 0.595> 0.05. Motivation of work has a significant effect on employee performance, this can be proved by the value of sig. the count is greater than 0.05 ie 0.727> 0.05. Work discipline has a significant effect on employee performance, this can be proven with sig value. the count is greater than 0.05 ie 0.056> 0.05. work environment, work motivation and work discipline has a proportion of influence on employee performance of 39.7% while the remaining 60.3% is influenced by other variables that are not in the linear regression model.